(untitled) (Nativa, 2023)
A intensificação da produção, vem instigando o desenvolvimento de novas tecnologias. O presente trabalho teve como objetivo avaliar a resposta no desenvolvimento vegetativo e produtivo da mandioca, frente a métodos de cultivos e aplicação de hormônios vegetais. Foram conduzidos dois experimentos a campo com a cultura da mandioca de mesa. (a) Primeiro experimento - 4 doses de biorregulador vegetal Stimulate® (0, 0,5, 1 e 1,5 L ha-1 do produto comercial) aplicadas via sulco de plantio sobre as manivas da variedade branca; e dois modos de preparo de solo, sendo um, subsolagem e gradagem e o outro sem preparo do solo. (b) Segundo experimento - 4 doses de biorregulador vegetal Stimulate® (0, 0,25, 0,5 e 1,0 L ha-1 do produto comercial); e dois modos de aplicação, sendo o primeiro via sulco de plantio sobre as manivas da variedade amarela, e o segundo via foliar aos 90 dias após o plantio (DAP). O plantio da mandioca sem o revolvimento do solo, indicam superioridade na quantidade, comprimento e produtividade de raízes, além de maior peso da parte aérea. A utilização de doses de bioestimulante, possibilitou maior desenvolvimento vegetativo em altura, diâmetro e peso da parte aérea, além de maior comprimento de raízes. Palavras-chave: manihot esculenta; hormônios vegetais; preparo solo. Optimization of vegetative growth and sweet cassava yield through biostimulant and cultivation methods ABSTRACT: The intensification of production in the same area has instigated the development of new technologies. The present work aimed to evaluate the response in the vegetative and productive development of sweet cassava, compared to cultivation methods and plant hormones application. Two field experiments were conducted with sweet cassava cultivation. (a) First experiment - 4 doses of plant bioregulator Stimulate® (0, 0.5, 1 and 1.5 L ha-1 of the commercial product) applied in planting furrow on the stems of the white variety; and two modes of soil preparation, one being subsoiling and harrowing and the other without soil preparation. (b) Second experiment - 4 doses of plant bioregulator Stimulate® (0, 0.25, 0.5, and 1.0 L ha-1 of the commercial product); and two modes of application, the first in planting furrows on the yellow variety stems and the second in the foliar application at 90 days after planting (DAP). Planting sweet cassava without disturbing the soil indicates superiority in the quantity, length and roots yield, and greater weight of the aerial part. The use of biostimulant doses allowed greater vegetative development in height, diameter and weight of the aerial part, in addition to greater root length. Keywords: manihot esculenta; plant hormones; soil tillage.